PENGARUH PEMBERIAN IBA DAN KOMPOSISI MEDIA TUMBUH TERHADAP PEMBENTUKAN AKAR DAN TUNAS SETEK TANAMAN MAWAR (Rosa sinensis) - Netti Herawati; Benni Satria; Annisa Najla Salsabila Apri; Silvia Permata Sari (Agros Journal of Agriculture Science, 2024)
This research aims to determine the interaction between IBA concentration and growth media composition. Apart from that, determine the provision of IBA and the best composition of growing media for the formation of roots and shoots of rose cuttings. This research was carried out for 4 months, starting from March to June 2022 at the UPT Farm Experimental Garden, Faculty of Agriculture, Andalas University, Padang. The design used was a Factorial Design with 2 factors arranged in a Completely Randomized Design (CRD). The first factor is the provision of IBA which consists of 4 levels (0; 50; 100; 150 ppm). The second factor is the composition of the growing medium which consists of 3 levels: (soil + charcoal husk + cow manure; soil + coconut fiber powder (cocopeat); soil + sand + cow manure). The research data were analyzed statistically using the F test at the 5% level. If the calculated F is greater than the F table of 5%, then proceed with the Duncan's New Multiple Range Test (DNMRT) at level 5. The results of the research show that there is no interaction between the concentration of IBA (Indole-3 butyric acid) and the composition of the growing media in root formation and rose cuttings. The best IBA concentration for forming roots and shoots from rose cuttings is a concentration of 100 ppm, while the best growing medium for forming roots and shoots from rose cuttings is soil + sand + cow manure.